How do Scores of DIT and MJT Differ? A Critical Assessment of the Use of Alternative Moral Development Scales in Studies of Business Ethics - Ishida, Chiharu (Journal of business ethics, 2006)
The construct of Cognitive Moral Development (CMD) has drawn much attention in the study of business ethics for over two decades. The Defining Issues Test (DIT) has made a significant contribution to the literature as an easy-to-administer CMD instrument, and the Moral Judgment Test (MJT), an alternative scale, has also been used widely especially in Europe. The two scales differ in their approaches to measuring CMD, focusing on stage preference (DIT) and stage consistency (MJT), yet empirical comparisons have been scarce. The present research empirically compares the two scales in terms of their correspondence with ethical ideology as a reference scale, and it demonstrates a clear distinction between the DIT and the MJT. Although they both aim to measure CMD, their dissimilar approaches lead to distinctly different implications.